Optimasi Pembiayaan Haji Di Indonesia: Peran Kontrak Wakalah - Zahrowaini, Taqiya; Nurganti, Nurganti; Marliyah, Marliyah; Halimatussakdiyah, Halimatussakdiyah (STAI Denpasar Bali, 2024)
The increase in Hajj registrants in Indonesia has led to the need for efficient and transparent management of Hajj funds. State regulations and Sharia principles must be adhered to when using Wakalah contracts for efficient management of Hajj funds. The aim of this research is to clarify the legal framework surrounding the Wakalah contract so that its implementation is more effective and optimizes the management of Hajj funds both in the context of sharia and state law. This research uses a normative juridical method, namely data is analyzed and processed systematically, logically and critically, using a normative approach and based on regulations, doctrine, legal principles and other relevant supplementary materials. Based on these findings, data was analyzed and a strong legal framework and sharia principles can maximize benefits for Hajj pilgrims and encourage cost-effective management of funds. Collaboration between Islamic banking institutions and Hajj regulators can also help overcome existing challenges. This research offers a deeper understanding of the benefits of ownership, Wakalah principles, as well as relevant legal and Sharia aspects, thanks to its careful methodological approach. Its unique contribution lies in its focus on beneficial ownership, a comprehensive examination of legal and sharia considerations, and the development of a practical framework for improving Hajj financial management in Indonesia.